Spatio-Temporal Using Geographically Weighted Panel Regression for Modeling Environmental Quality Index - Mar'ah, Zakiyah; Ruliana, Ruliana; Fikriani, Nurul Azurah; Ikhwana, Nur (Universitas Bumigora, 2025)
The Environmental Quality Index (EQI) represents a numerical measure used to assess Indonesia’s environmental conditions and is published annually by the Ministry of Environment and Forestry. In 2019, the EQI was recorded at 66.55, reflecting a decline of 5.12 points from 71.67 in 2018. This study aimed to analyze EQI across 34 Indonesian provinces during the 2018–2022 period using the Geographically Weighted Panel Regression (GWPR) approach. Data were obtained from the official Statistics Indonesia website. The purpose of employing GWPR was to capture both spatial and temporal variations in the factors influencing EQI, recognizing that environmental dynamics differ by region. Model selection tests for panel data indicated that the Fixed Effects Model (FEM) was the most appropriate specification. Therefore, GWPR was applied in combination with FEM to improve estimation accuracy. The results showed that the significant determinants of EQI varied across provinces, highlighting the heterogeneous nature of environmental challenges. The GWPR with Fixed Effect Model achieved a global R² of 84.38%, a substantial improvement compared to the 42.52% R2 from the conventional global Fixed Effect panel regression. This finding confirmed that GWPR provided stronger explanatory power by incorporating local variations into the analysis. The study concluded that adopting GWPR is essential for more precise modeling of environmental quality. Furthermore, the results highlighted the importance of region-specific environmental policies tailored to each province’s unique conditions in Indonesia